Application Of CPM Methode (Critical Path Methode) In Controlling The Time 100 Teus Contrainer Ship Hull Construction Project - Mia Syafrina; Fandy Bestario Harlan (Politeknik Negeri Batam, 2021)
Construction projects are generally the most high-risk businesses, especially shipbuilding projects. Efforts to reduce the risk can be done by minimizing the potential risk. This study aims to see potential high risk and prevent delays in the completion of ship construction using the Critical Path Method CPM at PT. XYZ. By using the Critical Path Method CPM critical paths can be given more attention so that they will not interfere ship construction projects. In addition, it is also a form of anticipation if there is a delay, it is possible to reschedule.